1990
DOI: 10.1088/0953-8984/2/31/012
|View full text |Cite
|
Sign up to set email alerts
|

Atomic short-range order and spin-glass behaviour in concentrated Cu-Mn alloys

Abstract: The effect of atomic short-range order (SRO) in Cu-Mn (5-30 at.% Mn) on the spin-glass properties is studied by measuring the magnetic behaviour and the low-temperature specific heat for two well defined equilibrium states of SRO. Usual spin-glass features are observed. The freezing temperatures Tf as well as the coefficient gamma * of the linear specific heat term appear to be not sensitive to SRO, whereas the amplitude of the peak susceptibility at Tf is drastically increased. The results are compared with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

1992
1992
1997
1997

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 19 publications
0
1
0
2
Order By: Relevance
“…Además, la fracción f á de átomos de soluto segregados a las dislocaciones puede evaluarse a partir de: [12] resultando un valor de 0,23. Por lo tanto, al final del proceso de segregación, la concentración residual de soluto c r = c (\-f¿) disponible para el desarrollo de orden disperso, es 0,154.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Además, la fracción f á de átomos de soluto segregados a las dislocaciones puede evaluarse a partir de: [12] resultando un valor de 0,23. Por lo tanto, al final del proceso de segregación, la concentración residual de soluto c r = c (\-f¿) disponible para el desarrollo de orden disperso, es 0,154.…”
Section: Discussionunclassified
“…Este estado ha sido observado en aleaciones aCu-Al (4-6), aFe-Al (7) y aCu-Zn (1 y 8-10), también se ha reportado en aleaciones aCu-Mn (11)(12)(13)(14). Además, se ha observado que en aleaciones aCu-Al deformadas en frío (15 y 16), la segregación de átomos de soluto hacia las dislocaciones parciales ocurre simultáneamente con el desarrollo de orden disperso.…”
Section: Introductionunclassified
“…The involvement of lattice defects was demonstrated by Gray and Smith [23,24] and Tustison and Beck [25]. Pfeiler and coworkers [26][27][28][29] found that the SRO relaxation time is unreasonably long below about 200 • C, and that therefore the equilibrium degree of SRO could practically be achieved only by aging above this temperature, where the equilibrium vacancy concentration becomes sufficient to drive the ordering process. The ensuing recommendation [27] that aging should be carried out at T = 210-260 • C discounts the reason for so many aging studies at temperatures near 100 • C, viz.…”
Section: Introductionmentioning
confidence: 99%